Documentation of Prescriptions and Clinical Outcomes in a Homeopathic Hospital Setting in West Bengal, India. (July 2015) - Saha, Subhranil; Koley, Munmun; Ghosh, Shubhamoy; Giri, Mohan; Das, Asim; Goenka, Rachna
Documentation of prescriptions and clinical outcomes in routine homeopathic practice is a prerequisite for conducting targeted research in homeopathy. Six homeopathic physicians participated in methodical data collection over a 3-month period in 6 outpatient departments of Mahesh Bhattacharyya Homeopathic Medical College and Hospital, West Bengal, India. A specifically designed Microsoft Excel spreadsheet enabled recording of consecutive appointments—date, patient identity, medical condition/complaint, whether chronic/acute, new/follow-up case, patient-assessed outcome (7-point Likert-type scale: −3 to +3), prescribed homeopathic medication, and whether other medication/s being taken for the condition. Spreadsheets were submitted monthly for data synthesis and analysis. A total of 1972 patients' follow-up generated data of 2905 appointments, of which 2272 (78.2%) were positive, 183 (6.3%) negative, and 450 (15.5%) showed no change. Strongly positive outcomes (scores of +2/+3) were recorded in osteoarthritis, piles, cough, dysfunctional uterine bleeding, chronic suppurative otitis media, and conjunctivitis. This systematic recording short-listed promising areas of future homeopathic research.